2012
DOI: 10.1103/physrevlett.108.045001
|View full text |Cite
|
Sign up to set email alerts
|

Local Kinetic Effects in Two-Dimensional Plasma Turbulence

Abstract: Using direct numerical simulations of a hybrid Vlasov-Maxwell model, kinetic processes are investigated in a two-dimensional turbulent plasma. In the turbulent regime, kinetic effects manifest through a deformation of the ion distribution function. These patterns of non-Maxwellian features are concentrated in space nearby regions of strong magnetic activity: the distribution function is modulated by the magnetic topology, and can elongate along or across the local magnetic field. These results open a new path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
236
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 196 publications
(254 citation statements)
references
References 26 publications
18
236
0
Order By: Relevance
“…Recently, a PVIbased method was implemented to search for solar wind reconnection sites. The method was tested in the context of MHD simulation [95], where current sheets and reconnection rates can be unambiguously identified by full analysis of the MHD fields. It was found that, for strong events with PVI >6 or 7, it was extremely likely that these would also be located at reconnecting current sheets.…”
Section: Evidence For Coherent Structures In the Solar Windmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a PVIbased method was implemented to search for solar wind reconnection sites. The method was tested in the context of MHD simulation [95], where current sheets and reconnection rates can be unambiguously identified by full analysis of the MHD fields. It was found that, for strong events with PVI >6 or 7, it was extremely likely that these would also be located at reconnecting current sheets.…”
Section: Evidence For Coherent Structures In the Solar Windmentioning
confidence: 99%
“…Eulerian Vlasov) [95,139]. This method is computationally very expensive but has the distinct advantage of resolving with good fidelity and resolution various properties of the plasma velocity distribution functions.…”
Section: Plasma Intermittency At Kinetic Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this interpretation, current sheets are characteristic coherent structures expected in active intermittent MHD turbulence and are therefore integral to the dynamical couplings across scales. It is quite possible that discontinuities are related to both flux tube boundaries and intermittent structures that appear spontaneously in MHD turbulence (Matthaeus and Montgomery 1980;Matthaeus et al 1986b;Carbone et al 1990; Veltri and Mangeney 1999; Vasquez (Osman et al 2011;Servidio et al 2012;Wan et al 2012;Perrone et al 2013;Wu et al 2013). There is evidence suggesting that increased helium, proton and electron temperature anisotropies are linked to near-discontinuous structures.…”
Section: Electron Scale Turbulencementioning
confidence: 99%